2007
DOI: 10.1242/dev.02697
|View full text |Cite
|
Sign up to set email alerts
|

Functional redundancy among Nanos proteins and a distinct role of Nanos2 during male germ cell development

Abstract: The mouse Nanos proteins, Nanos2 and Nanos3, are required for germ cell development and share a highly conserved zinc-finger domain. The expression patterns of these factors during development, however, differ from each other. Nanos3 expression in the mouse embryo commences in the primordial germ cells (PGCs) just after their formation, and a loss of this protein results in the germ cell-less phenotype in both sexes. By contrast, Nanos2 expression begins only in male PGCs after their entry into the genital rid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 19 publications
3
101
1
1
Order By: Relevance
“…The repression was orientation-dependent, and the reporter gene complementary to the piRNAs was more effectively repressed, suggesting that it was, indeed, dependent on piRNA generation. Considering the studies on other transgenes in the mouse testis (Wang et al 2006;Suzuki et al 2007), we believe that transgene insertions outside of piRNA generating regions would not result in a silencing effect. The repression was, at least in part, due to accelerated degradation of the target RNA (PTGS) and clearly dependent on the piRNA pathway, as overexpression of PIWIL2 enhanced the repression.…”
Section: Discussionmentioning
confidence: 99%
“…The repression was orientation-dependent, and the reporter gene complementary to the piRNAs was more effectively repressed, suggesting that it was, indeed, dependent on piRNA generation. Considering the studies on other transgenes in the mouse testis (Wang et al 2006;Suzuki et al 2007), we believe that transgene insertions outside of piRNA generating regions would not result in a silencing effect. The repression was, at least in part, due to accelerated degradation of the target RNA (PTGS) and clearly dependent on the piRNA pathway, as overexpression of PIWIL2 enhanced the repression.…”
Section: Discussionmentioning
confidence: 99%
“…In further immunoprecipitation experiments, we used a transgenic mouse line expressing a FLAG-tagged NANOS2 under the direct control of the Nanos2 enhancer (15) (Fig. S5A), since we had confirmed that this fusion protein was functional (Fig.…”
Section: Nanos2 Interacts With the Ccr4-not Deadenylation Complex Andmentioning
confidence: 99%
“…SCF/cKIT signalling is required for proliferation and survival of germ cells and aberrant function of this pathway has been associated with abnormal proliferation and transformation of germ cells Godin and Wylie, 1991;Matsui et al, 1991;Dolci et al, 1993;Pesce et al, 1993;Donovan and de Miguel, 2003;Sakuma et al, 2003;McIntyre et al, 2005;Goddard et al, 2007). Two members of the NANOS family of RNA binding proteins, NANOS2 and NANOS3 are also required for survival of foetal germ cells (Tsuda et al, 2003;Suzuki et al, 2007). Nanos3 is expressed in migrating germ cells and functions to maintain early germ cell survival, at least partly through suppression of apoptosis , while Nanos2 is male specifically expressed and required for survival and differentiation of gonadal germ cells (Suzuki et.…”
Section: Survival and Proliferation: Key Aspects Of Early Germ Cell Dmentioning
confidence: 99%